(untitled) (International Journal of Physiotherapy, 2016)
Background: Physiotherapy is an essentialtreatment in the management of Mechanical Neck ache, still there was lack of literature seen supporting the effectiveness of Physiotherapy interventions with their doses targeting specific group of population. The focus of study was to see the effectiveness of Kaltenborn Grade III mobilization, Muscle Energy Techniques and their combination to improve range and functional ability in patients with Mechanical Neck ache. Methods: 72 patients with Mechanical Neck achewere randomly categorized in 3 groups (Mobilization, METs and Combination group. NDI scale and goniometry was used as an assessment tool to measure the outcome before and after treatment (follow up 1 week). Results: According to the results there was significant improvement seen in Combination group (Mobilization and METs) in terms of pain, which decreased from 7.70±0.69 to 1.25±1.93 (p=0.00), gain in ROM e.g. Cervical Flexion (27.29±2.38 to 37.54±3.14). Whereas, marked significance (p=0.00) was seen in the NDI score and percentage of Combination group. ANOVA tells us that difference was significant in all three groups in categories of pain (VAS), gain in cervical ranges and NDI score and percentage as p=0.00. Combination group had significant difference within the groups then METs and Mobilization group in all categories of VAS, Cervical ranges, NDI score and percentage. Conclusion: Combination of (Grade III Kaltenborn and METs) was seen more effective in terms of improving Mechanical Neck Pain, in smaller treatment session (7 days only).